Integrated multi-omics analysis reveals the underlying molecular mechanism for the neurotoxicity of triclosan in zebrafish - Shasha Zhao; Yuhang Ling; Baohua Zhang; Danting Wang; Limei Sun (Ecotoxicology and Environmental Safety)
Triclosan (TCS) is a primary broad-spectrum antibacterial agent commonly present in the environment. As a new type of environmental endocrine disruptor, it causes range of toxicities, including hepatotoxicity and reproductive toxicity. However, few research has examined the toxicity of long-term TCS-induced exposure in zebrafish at ambient concentrations, in contrast to the early life stage investigations. In the present study, we investigated the behavioral effects of TCS at environmental concentrations (300 μg/L) during constant exposure in zebrafish adults；An integrated transcriptomic and metabolomic analysis was performed to analyze the molecular mechanism underlying behavioral effects of TCS. Our results show that TCS exposure significantly induces behavioral disruptions such as anxiety-like behavior, memory problems, and altered social preferences. Histopathological investigations and neural ultrastructural observations demonstrated that TCS could induce variable levels of pyknosis and vacuolation in the cytoplasm of neurons as well as torn mitochondrial membranes, shrinkage and broken or absent cristae. Transcriptomics indicated that immune- and metabolism-related gene expression patterns were severely disturbed by TCS. Metabolomic analysis revealed 82 distinct metabolites in adult zebrafish exposed to TCS. Lipid metabolism, especially glycerophospholipid metabolism, and amino acid regulation pathways were co-enriched by multi-omics combinatorial analysis. Hence, this study highlights a number of biomarkers for the risk assessment of TCS against non-target organisms, offering a reference dataset for the behavioral toxicity of TCS to zebrafish, and strengthening the early warning, management, and control of TCS pollution.